DEVELOPMENT OF E-MODULES ASSISTED BY FLIPBOOK APPLICATIONS IN MARKETING SUBJECTS IN VOCATIONAL SCHOOLS - Suharsono, Naswan; Sufi, Lintang; Hidayat, Rachmad (PT. BATARI EDU CALYA, 2023)
Learning media can contribute to improving learning outcomes. By using the right media, learners can help students learn more productively, interactively, and according to their characteristics. This research was conducted to produce media, using the Borg and Gall development model. The activity begins with the analysis of learner needs, followed by the identification of components and the design of products that are ready to be tested and revised so that they can be optimally utilized. This development research produces Flipbook-Based e-book Learning Media using Canva and Flipbook Maker Software, which can be used in Basic Marketing Subjects, professional field worker training programs, or for prospective entrepreneurs in the marketing field. Product trials were carried out in three stages, through expert testing, small group testing, and field testing stages following the education calendar in vocational schools. At the end of each testing stage, evaluation and revision activities are carried out, so that the final product can reach the ready-to-use level and has the feasibility to be utilized